Modelling Cambodia’s Foreign Exchange Rate Dynamics: A Markov-Switching Autoregressive Model - Lim, Siphat (International Journal of Economics and Financial Issues, 2024)
The analysis of the daily fluctuations in the foreign exchange rate between the Khmer Riel and the US dollar was performed utilizing a Markov- switching autoregressive model. This study covered a time frame from January 04, 2005, to August 22, 2024, encompassing a total of 4989 days of data. The research findings revealed that the MS(2)-AR(1) model emerged as the most appropriate model for the analysis. The empirical results from both state 1 and state 2 models demonstrated that the intercept term, along with the AR(1) component, exerted a statistically significant positive effect on the exchange rate at a 1% significance level. Furthermore, the intercept term, which represents the average exchange rate, along with the volatility of the exchange rate in the state 2 model, was found to be higher than that observed in the state 1 model. The analysis of the probability transition matrix indicated that there was a 15.53% likelihood for FX to transition from state 2 to state 1. In contrast, the probability of FX departing from state 1 and returning to state 2 was recorded at 29.34%. Additionally, the chance of FX maintaining its position in state 1 was assessed to be 70.66%, while the probability of it remaining in state 2 was significantly higher at 84.47%.